AKUNTANSI FORENSIK: SEBUAH ALTERNATIF PROFESI AKUNTANSI - Sururi . (Akademi Akuntansi YKPN Yogyakarta, 2008)
The increasing demand of sound practice in conducting the operation of organization as well as the increasing cases of fraud and intentional misleading of financial information have triggered the emerging and developing forensic auditing. The main objective of the forensic auditing is to proof the conformity of the business operation with the legal requirements as well as to detect, to prevent, and to proof the possible offense to the legal requirement which are committed by management or persons inside the organization. The forensic auditing becomes very important to any business because any form of illegal or unauthorized business process can be very harmful either to the company itself or to the stakeholders, if not in the short run probably will be in the long run. To response the increasing demand of forensic audit, presently has been developed what the so called as a forensic accounting. The main objective of the forensic accounting is to provide the accounting systems and accounting practices which are conform to the legal requirements.Keyword: Forensic Auditing, Forensic Accounting